Impacts of organisational culture and religiosity on employee engagement: the moderating role of ocb in selected mining companies in Ghana - Acheampong, Prisca Oteng; Mohammed Kamil, Naail; Musah, Mohammed Borhandden; Zakari, Mariama (GADING Journal for the Social Sciences, 2024)
This study examines the impact of organisational culture and religiosity on employee engagement, and the moderating effects of employee organisational citizenship behaviour in mining companies. The study employs the descriptive cross-sectional survey design. The population was the employees who work within the nine selected companies in the mining industry of Ghana namely Adamus Resources Ltd, Asanko Gold Ghana Limited, Gold Fields Ghana Tarkwa Mine, Chirano Gold Mine, Golden Star Bogoso/Prestea Ltd, Golden Star Wassa Mine, Newmont Ghana Ahafo Mine, Newmont Ghana Akyem Mine, and Perseus Mining Ltd. The researchers adopted simple random sampling technique to select 245 respondents. Quantitative data were collected through questionnaire administration. The Statistical Package for Social Science (SPSS) version 24.0 was used to analyse the data. The results revealed that organisational culture and organisational citizenship behaviour (OCB) have a positive influence on employee engagement. OCB has a significant moderating effect on the relationship between Religiosity and Employee Engagement. Companies within the mining industry can implement the findings of this study to improve the level of employee engagement, a key factor that helps them realize their objectives. This study has proved further that the moderating effect of OCB on religiosity can enhance employee engagement.